Multimedia Pembelajaran untuk Melatih Kecerdasan Majemuk pada Anak Usia Dini - Sisca Rahmadonna (MAJALAH ILMIAH PEMBELAJARAN, 2009)
This research aims at developing learning multimedia which can be used to effectively stimulate multiple intelligence specially verbal linguistic intelligence, logical-mathematical intelligence, and spatial intelligence in early childhood.The subjects of the research are children between 3 to 5 years old. This research is conducted in “Warna Warni” Childhood Nursery and Education Centre using research and development. The development is done within several steps: (1) pre study, (2) development process, (3) field testing, and (4) socialization. Pre study consists of literature and field studies. The development process includes purpose analysis, ability analysis, multimedia design development, material and media expert validation. Field experiment comprises preliminary field testing, main field testing, operational field testing. The instruments used in this research include evaluation observation sheet and interview guidelines.The research and development findings show that generally all aspects in developed learning multimedia are considered satisfactory. This judgement can be seen either from complement observation or evaluation results which cover material, learning strategy and technical qualities. The observation result in terms of material quality yields a mean of 4.50; learning strategy 4.40; and technical quality 4.14. The mean score of complement evaluation result in terms of material quality is 4.46; learning strategy 4.40; and teaching strategy 4.50. All these means fall in a very good criterion. Based on these means, the developed learning multimedia in this research can be used to stimulate multiple intelligence in early childhood.